2021
DOI: 10.3390/ma14185451
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Metal Embrittlement of Advanced High Strength Steel: Experiments and Damage Modeling

Abstract: In the automotive industry, corrosion protected galvanized advanced high strength steels with high ductility (AHSS-HD) gain importance due to their good formability and their lightweight potential. Unfortunately, under specific thermomechanical loading conditions such as during resistance spot welding galvanized, AHSS-HD sheets tend to show liquid metal embrittlement (LME). LME is an intergranular decohesion phenomenon leading to a drastic loss of ductility of up to 95%. The occurrence of LME for a given galva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…6 Differences in HTTT parameters such as set temperature, hold time, and strain rate can result in discrepancies in the thermal cycles and LME cracking behaviour. Moreover, it has been shown that these parameters can influence the morphology and microstructure of the Fe-Zn intermetallic in the coating layer, which is critical to LME cracking behaviour assessment 7,8 Discrepancies in the Fe-Zn intermetallic compound morphology between HTTT and RSW have been reported and attributed to different thermal cycles of each process. 6 In the case of finite-element modelling, DiGiovanni et al 9 demonstrated that a correlation exists between electrode collapse and thermal stresses, especially in the shoulder area of the weldment.…”
Section: Introductionmentioning
confidence: 99%
“…6 Differences in HTTT parameters such as set temperature, hold time, and strain rate can result in discrepancies in the thermal cycles and LME cracking behaviour. Moreover, it has been shown that these parameters can influence the morphology and microstructure of the Fe-Zn intermetallic in the coating layer, which is critical to LME cracking behaviour assessment 7,8 Discrepancies in the Fe-Zn intermetallic compound morphology between HTTT and RSW have been reported and attributed to different thermal cycles of each process. 6 In the case of finite-element modelling, DiGiovanni et al 9 demonstrated that a correlation exists between electrode collapse and thermal stresses, especially in the shoulder area of the weldment.…”
Section: Introductionmentioning
confidence: 99%
“…Zn can embrittle the steel, and macroscopic cracks can occur during the further processing steps. Grain boundary (GB) weakening by Zn is supposed to be the underlying mechanism of this metal-induced embrittlement (MIE), which is therefore highly influenced by different alloy compositions and their resulting microstructures [3][4][5][6]. Already a monolayer or even a sub-monolayer of Zn at a GB has a strong impact on its strength [7].…”
Section: Introductionmentioning
confidence: 99%